Impact of German Students’ Digital Readiness for Online- Learning on Factors of Challenges and Mediating Role of German Teachers’ Support at Foreign Languages Universities in Myanmar during COVID- 19 Pandemic: Perspectives from Developing Country - Win, Sai Si Thu; Swe, Sein U (Future Science)
The purpose of this study is to examine the connection between German students’ digital readiness for online learning, their challenges and the support of German teachers at Foreign Languages Universities in Myanmar. The COVID-19 pandemic has impacted educational institutions across the world. In Myanmar, all the learning methods shifted to online instruction. However, there are a limited number of factors that influence students’ online learning. Some of these include digital readiness and support from teachers. In addition, several challenges exist regarding their educational backgrounds. The data for this research were collected through conducting in-depth interviews with German teachers (n=10) and surveys of German students (n=112). This study took an exploratory mixed-method design. In qualitative analysis, the constructivist grounded theory method is used for data collection and the data analysis is also described and justified by Charmaz (2014) as a general guide. In the quantitative analysis, the data were analyzed using descriptive statistics through SPSS 27.0. Findings reveal that German students faced a limited number of challenges and the level of German student’s digital readiness and teachers’ support positively impacted on these factors of challenges for online learning during Covid-19 pandemic. The data analyzed showed that each of their challenges varied according to their perceptions and readiness to technology integration. To sum up, this research offers factors of challenges which significantly correlate with digital readiness and teachers’ support during the corona-crisis in developing country.